RHYTHMIC GYMNASTICS AS EDUCATION AND PERSONAL DEVELOPMENT OF FEMALE STUDENTS - Muratova Gulnara Rashitovna; Shodiev Ergashali Kudratshoevich (Galaxy International Interdisciplinary Research Journal, 2024)
This article examines the formation of the personality of female students through rhythmic gymnastics classes. Types of rhythmic gymnastics and aerobics.